A kind of aluminum liquid nickel removal agent and preparation method thereof
By using components such as aluminum fluoride and spherical nanoalumina in the aluminum liquid nickel remover to generate nickel fluoride and eutectics, the problem of difficulty in removing nickel in different dispersion states in the aluminum liquid is solved, and nickel is realized Efficient removal and improved aluminum product performance.
Patent Information
- Application Number
- CN202411005025.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-25
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-07-25
AI Technical Summary
Existing aluminum liquid nickel removers are difficult to effectively remove nickel in different dispersed states in aluminum liquid, resulting in an exceeding the standard nickel content, affecting the performance and application range of aluminum products.
Using a liquid nickel remover of aluminum, including aluminum fluoride, magnesium chloride, sodium chloride, zinc chloride and spherical nanoalumina, nickel fluoride is formed by reacting aluminum fluoride with nickel, and using a specific proportion of other compounds to form a co- Crystals inhibit side reactions and promote the removal of nickel.
It realizes the full and effective removal of nickel in liquid aluminum, reduces the nickel content, improves the corrosion resistance and service life of aluminum products, and expands its application range.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal smelting, and more specifically, relates to a nickel removal agent for aluminum liquid and a preparation method thereof. Background Art
[0002] There is a small amount of impurity nickel in the carbon anode for aluminum. As the anode is consumed, it will gradually enter the aluminum liquid, resulting in excessive nickel content, thus affecting the performance of the product. It will not only reduce the corrosion resistance of aluminum products, ultimately affecting their service life, but also easily lead to excessive heavy metals when aluminum products are used as food-grade materials due to excessive nickel content, ultimately limiting the scope of application of aluminum products.
[0003] The nickel content in raw aluminum is generally above 100ppm. At present, the nickel removal methods for producing high-purity aluminum include three-layer liquid electrolytic refining, segregation method, etc., which can reduce the nickel content to less than 60ppm. However, the above methods require large energy consumption and high production costs. Patent CN201110459359.1 discloses a nickel remover for aluminum liquid, which includes 50%-80% zirconium-containing compound, 10%-35% activated alumina, and 5-15% bentonite. In the patent technical solution, the good ion exchangeability of bentonite and the strong adsorption of nickel by the micropores on the surface of activated alumina are mainly utilized to reduce the nickel content in aluminum liquid, while the zirconium-containing compound can form a high-density compound with aluminum liquid to precipitate and finally achieve the purpose of nickel removal. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the problem that the existing aluminum liquid nickel remover uses simple bentonite to adsorb nickel, which is difficult to effectively and fully remove nickel in different dispersed states in the aluminum liquid, and provides an aluminum liquid nickel remover and a preparation method thereof.
[0005] The purpose of the present invention is to provide a nickel removing agent for aluminum liquid.
[0006] Another object of the present invention is to provide a method for preparing a nickel remover for aluminum liquid.
[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0008] A nickel remover for aluminum liquid comprises the following raw materials in parts by weight: 10-12 parts of aluminum fluoride, 4-6 parts of magnesium chloride, 2-2.5 parts of sodium chloride, 0.9-1.2 parts of zinc chloride, and 75-80 parts of spherical nano-alumina; wherein the sphericity of the spherical nano-alumina is 8.8-9.2; and the D50 of the spherical nano-alumina is 50-60nm.
[0009] The above technical solution first adds aluminum fluoride, which can react with nickel in the aluminum liquid under high temperature environment to generate nickel fluoride, thereby removing the nickel element from the aluminum liquid; in addition, thanks to the presence of magnesium chloride, sodium chloride and zinc chloride in a specific proportion, the generated nickel fluoride is easily captured by them to form a eutectic. The formation of the eutectic can inhibit the possibility of further side reactions of nickel fluoride in the aluminum liquid. In addition, it can also promote the effective separation between aluminum ash and aluminum liquid, so that the nickel element can be removed smoothly. In addition, the inventors found that after a relatively large amount of aluminum fluoride is added, a part of it can participate in the reaction with nickel, and a part of it can remain to participate in the formation process of the above-mentioned eutectic, thereby accelerating the formation of the eutectic; furthermore, if only the aforementioned functional additives are added, the effect is limited. This is because the inventors found that the addition of the above-mentioned various substances in the aluminum liquid is limited, which makes it difficult for it to effectively contact with nickel. In addition, it is also difficult to effectively disperse it in the aluminum liquid. However, this technical problem can be solved by adding spherical nano-alumina of a certain size and sphericity; specifically, nano-sized spherical alumina can effectively contact with aluminum liquid under high temperature conditions of aluminum liquid, and the relatively high sphericity ensures the uniform spreading of aluminum liquid on its surface, thereby providing a place for the above-mentioned functional additives to react with aluminum liquid, and once a eutectic is produced, it can be adsorbed due to the higher surface energy of the nanoparticles, and finally enter the aluminum ash together, achieving the purpose of sufficient and effective impurity removal.
[0010] Furthermore, the D50 of the spherical nano-alumina is 52-54 nm, and the particle size distribution range of the spherical nano-alumina is 5-120 nm.
[0011] By selecting spherical nano-alumina with a wide particle size distribution range, it can provide reaction sites for the aforementioned functional additives and aluminum liquid with different specific surface areas, thereby ensuring that the nickel in the aluminum liquid can fully react with the functional additives. In addition, since particles of different sizes diffuse more randomly, the possibility of contacting nickel in different parts of the aluminum liquid will also be significantly increased, thereby increasing the removal rate of aluminum and nickel elements.
[0012] Furthermore, the porosity of the spherical nano-alumina is 20-25%, and the pores of the spherical nano-alumina are through holes.
[0013] Furthermore, the spherical nano-alumina further comprises amorphous carbon coated on the surface of the spherical nano-alumina, and the coating amount of the amorphous carbon is 4.2-4.8% of the mass of the spherical nano-alumina.
[0014] Furthermore, it also includes cryolite with a mass 1.2-1.4 times that of the aluminum fluoride.
[0015] Furthermore, it also includes cerium chloride accounting for 10-15% of the mass of the aluminum fluoride and strontium chloride accounting for 3-3.2% of the mass of the aluminum fluoride.
[0016] A method for preparing a nickel remover for aluminum liquid, the specific preparation steps comprising: carbon coating of spherical nano-alumina: subjecting the spherical nano-alumina to chemical vapor deposition so that an organic precursor is coated on the surface of the spherical nano-alumina, and then naturally cooling to room temperature in an inert gas atmosphere to obtain carbon-coated spherical nano-alumina; product preparation: weighing each component according to the composition of the raw materials, first ball-milling aluminum fluoride, magnesium chloride, zinc chloride and sodium chloride to mix evenly, and then stirring and mixing with the carbon-coated spherical nano-alumina to obtain the product.
[0017] Furthermore, the chemical vapor deposition includes: using acetylene gas as a carbon source, performing chemical vapor deposition at a temperature of 1000-1100°C and a gas flow rate of 380-400L / min, and by adjusting the specific chemical vapor deposition time, the amount of amorphous carbon coating on the surface of the spherical nano-alumina is adjusted to 4.2-4.8% of the mass of the spherical nano-alumina. DETAILED DESCRIPTION
[0018] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0019] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0020] Example 1
[0021] Add spherical nano-alumina into a tube furnace, heat it to 1000°C at a rate of 3°C / min, then continuously introduce acetylene gas into the tube furnace at a rate of 380L / min, continuously deposit amorphous carbon on the surface of the spherical nano-alumina, and adjust the deposition time so that the coating amount of amorphous carbon on the surface of the spherical nano-alumina is 4.2% of the mass of the spherical nano-alumina. After the deposition is completed, naturally cool it to room temperature in a nitrogen atmosphere to obtain carbon-coated spherical nano-alumina;
[0022] The D50 of the spherical nano-alumina is 52 nm, and the particle size distribution range of the spherical nano-alumina is 7-120 nm; the porosity of the spherical nano-alumina is 20%, and the pores of the spherical nano-alumina are through holes;
[0023] Take, in parts by weight, 10 parts of aluminum fluoride, 4 parts of magnesium chloride, 2 parts of sodium chloride, 0.9 parts of zinc chloride, and 75 parts of carbon-coated spherical nano-alumina; and 10% of the weight of the aluminum fluoride, and 3% of the weight of the aluminum fluoride, and 1.2 times the weight of the aluminum fluoride, of cerium chloride;
[0024] First, aluminum fluoride, magnesium chloride, sodium chloride, zinc chloride, cerium chloride, strontium chloride and cryolite are mixed and poured into a ball mill, 0.8 times the mass of aluminum fluoride ethylene glycol is added as a grinding aid, and zirconium oxide ball milling beads are added according to a ball-to-material mass ratio of 30:1, and the ball milling is continued for 2 hours at an autorotation speed of 180 r / min and an orbital speed of 420 r / min. After the ball milling is completed, the ball milling is dried to remove residual ethylene glycol to obtain a ball mill material; wherein the ball-to-material mass ratio is: the ratio of the mass of the zirconium oxide ball milling beads to the total mass of aluminum fluoride, magnesium chloride, sodium chloride, zinc chloride, cerium chloride, strontium chloride and cryolite;
[0025] Then, the ball abrasive and carbon-coated spherical nano-alumina were mixed, and the mixture was stirred for 3 hours at a stirring speed of 650 r / min. Then, the material was discharged to obtain the product of aluminum liquid nickel remover.
[0026] Example 2
[0027] Add spherical nano-alumina into a tube furnace, heat it to 1050°C at a rate of 5°C / min, then continuously introduce acetylene gas into the tube furnace at a rate of 390L / min, continuously deposit amorphous carbon on the surface of the spherical nano-alumina, and adjust the deposition time so that the coating amount of amorphous carbon on the surface of the spherical nano-alumina is 4.5% of the mass of the spherical nano-alumina. After the deposition is completed, naturally cool it to room temperature in a nitrogen atmosphere to obtain carbon-coated spherical nano-alumina;
[0028] The D50 of the spherical nano-alumina is 53 nm, and the particle size distribution range of the spherical nano-alumina is 9-110 nm; the porosity of the spherical nano-alumina is 22%, and the pores of the spherical nano-alumina are through holes;
[0029] Take, in parts by weight, 11 parts of aluminum fluoride, 5 parts of magnesium chloride, 2.3 parts of sodium chloride, 1.1 parts of zinc chloride, and 78 parts of carbon-coated spherical nano-alumina; and 12% of the weight of the aluminum fluoride, 3.1% of the weight of the aluminum fluoride, and 1.3 times the weight of the aluminum fluoride, of cerium chloride;
[0030] First, aluminum fluoride, magnesium chloride, sodium chloride, zinc chloride, cerium chloride, strontium chloride and cryolite are mixed and poured into a ball mill, ethylene glycol in an amount of 1.0 times the mass of aluminum fluoride is added as a grinding aid, and zirconium oxide ball milling beads are added at a ball-to-material mass ratio of 30:1, and the ball milling is continued for 3 hours at an autorotation speed of 190 r / min and an orbital speed of 430 r / min. After the ball milling is completed, the ball milling is dried to remove residual ethylene glycol, and the ball mill material is obtained; wherein the ball-to-material mass ratio is: the ratio of the mass of the zirconium oxide ball milling beads to the total mass of aluminum fluoride, magnesium chloride, sodium chloride, zinc chloride, cerium chloride, strontium chloride and cryolite;
[0031] Then, the ball abrasive and carbon-coated spherical nano-alumina were mixed, and the mixture was stirred for 4 hours at a stirring speed of 680 r / min. Then, the mixture was discharged to obtain the product of aluminum liquid nickel remover.
[0032] Example 3
[0033] Add spherical nano-alumina into a tube furnace, heat it to 1100°C at a rate of 6°C / min, then continuously introduce acetylene gas into the tube furnace at a rate of 400L / min, continuously deposit amorphous carbon on the surface of the spherical nano-alumina, and adjust the deposition time so that the coating amount of amorphous carbon on the surface of the spherical nano-alumina is 4.8% of the mass of the spherical nano-alumina. After the deposition is completed, naturally cool it to room temperature in a nitrogen atmosphere to obtain carbon-coated spherical nano-alumina;
[0034] The D50 of the spherical nano-alumina is 54 nm, and the particle size distribution range of the spherical nano-alumina is 8-118 nm; the porosity of the spherical nano-alumina is 25%, and the pores of the spherical nano-alumina are through holes;
[0035] Take, in parts by weight, 12 parts of aluminum fluoride, 6 parts of magnesium chloride, 2.5 parts of sodium chloride, 1.2 parts of zinc chloride, and 80 parts of carbon-coated spherical nano-alumina; and 15% of the weight of the aluminum fluoride, and 3.2% of the weight of the aluminum fluoride, and 1.4 times the weight of the aluminum fluoride, of cerium chloride;
[0036] First, aluminum fluoride, magnesium chloride, sodium chloride, zinc chloride, cerium chloride, strontium chloride and cryolite are mixed and poured into a ball mill, ethylene glycol in an amount of 1.2 times the mass of aluminum fluoride is added as a grinding aid, and zirconium oxide ball milling beads are added at a ball-to-material mass ratio of 30:1, and the ball milling is continued for 4 hours at an autorotation speed of 200 r / min and an orbital speed of 450 r / min. After the ball milling is completed, the mixture is dried to remove residual ethylene glycol, and a ball mill material is obtained; wherein the ball-to-material mass ratio is: the ratio of the mass of the zirconium oxide ball milling beads to the total mass of aluminum fluoride, magnesium chloride, sodium chloride, zinc chloride, cerium chloride, strontium chloride and cryolite;
[0037] Then, the ball abrasive and the carbon-coated spherical nano-alumina were mixed, and the mixture was stirred for 5 hours at a stirring speed of 700 r / min. Then, the mixture was discharged to obtain the product of aluminum liquid nickel remover.
[0038] Example 4
[0039] The present embodiment differs from the embodiment 1 in that cerium chloride and strontium chloride are not added, and the other conditions remain unchanged.
[0040] Example 5
[0041] The present embodiment differs from the embodiment 1 in that the spherical nano-alumina is not carbon coated, and the other conditions remain unchanged.
[0042] Specific:
[0043] Take, in parts by weight, 10 parts of aluminum fluoride, 4 parts of magnesium chloride, 2 parts of sodium chloride, 0.9 parts of zinc chloride, and 75 parts of spherical nano-alumina; and 10% of the weight of the aluminum fluoride, 3% of the weight of the aluminum fluoride, and 1.2 times the weight of the aluminum fluoride, of cerium chloride;
[0044] The D50 of the spherical nano-alumina is 52nm, and the particle size distribution range of the spherical nano-alumina is 7-120nm; the porosity of the spherical nano-alumina is 20%, and the pores of the spherical nano-alumina are through holes;
[0045] First, aluminum fluoride, magnesium chloride, sodium chloride, zinc chloride, cerium chloride, strontium chloride and cryolite are mixed and poured into a ball mill, 0.8 times the mass of aluminum fluoride ethylene glycol is added as a grinding aid, and zirconium oxide ball milling beads are added according to a ball-to-material mass ratio of 30:1, and the ball milling is continued for 2 hours at an autorotation speed of 180 r / min and an orbital speed of 420 r / min. After the ball milling is completed, the ball milling is dried to remove residual ethylene glycol to obtain a ball mill material; wherein the ball-to-material mass ratio is: the ratio of the mass of the zirconium oxide ball milling beads to the total mass of aluminum fluoride, magnesium chloride, sodium chloride, zinc chloride, cerium chloride, strontium chloride and cryolite;
[0046] Then, the ball abrasive and carbon-coated spherical nano-alumina were mixed, and the mixture was stirred for 3 hours at a stirring speed of 650 r / min. Then, the material was discharged to obtain the product of aluminum liquid nickel remover.
[0047] Comparative Example 1
[0048] The difference between this comparative example and Example 1 is that an equal amount of aluminum chloride is used to replace aluminum fluoride, and other conditions remain unchanged.
[0049] Comparative Example 2
[0050] The difference between this comparative example and Example 1 is that equal amounts of aluminum chloride are used to replace sodium chloride, zinc chloride and magnesium chloride, and other conditions remain unchanged.
[0051] The performance tests were performed on the products obtained in Examples 1-5 and Comparative Examples 1-2. The specific test methods and test results are as follows:
[0052] Take an aluminum ingot and calibrate its initial nickel content to obtain an initial nickel content m;
[0053] After the aluminum ingot is melted to obtain aluminum liquid, the products obtained in the above embodiment or comparative example are added respectively according to the amount of the aluminum liquid nickel remover being 0.1% of the mass of the aluminum liquid;
[0054] Specifically, nitrogen is added to the aluminum liquid by blowing through the purification pipeline, the nitrogen pressure is controlled to be 0.1MPa, and the rolling height of the aluminum liquid is controlled to be within 15cm. During the purification process, the purification pipeline is close to the bottom of the furnace and moves slowly in the furnace to purify every corner;
[0055] After the nickel removal agent is added, continue blowing with nitrogen for 10 seconds, then stop and use a slag rake to remove the slag;
[0056] After the slag removal is completed, the aluminum liquid is cast into aluminum bars, and the nickel content n in the aluminum bars is tested again;
[0057] Removal rate = ((mn) / m) × 100%;
[0058] The specific test results are shown in Table 1:
[0059] Removal rate / % Example 1 96.5 Example 2 96.9 Example 3 96.3 Example 4 93.5 Example 5 92.1 Comparative Example 1 85.6 Comparative Example 2 80.1
[0060] It can be seen from the test results in Table 1 that the product obtained by the present invention can effectively remove the nickel element in the aluminum liquid during the aluminum liquid impurity removal process.
[0061] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A nickel removal agent for aluminum liquid, characterized in that: The raw materials include the following parts by weight: 10-12 parts of aluminum fluoride, 4-6 parts of magnesium chloride, 2-2.5 parts of sodium chloride, 0.9-1.2 parts of zinc chloride, and 75-80 parts of spherical nano-alumina; Wherein, the sphericity of the spherical nano-alumina is 8.8-9.2; The D50 of the spherical nano-alumina is 50-60nm; The porosity of the spherical nano-alumina is 20-25%, and the pores of the spherical nano-alumina are through holes; The spherical nano-alumina further comprises amorphous carbon coated on the surface of the spherical nano-alumina, and the coating amount of the amorphous carbon is 4.2-4.8% of the mass of the spherical nano-alumina.
2. The nickel removing agent for aluminum liquid according to claim 1, characterized in that: The D50 of the spherical nano-alumina is 52-54 nm, and the particle size distribution range of the spherical nano-alumina is 5-120 nm.
3. The nickel removing agent for aluminum liquid according to claim 1, characterized in that: It also includes cryolite with a mass 1.2-1.4 times that of the aluminum fluoride.
4. The nickel removing agent for aluminum liquid according to claim 1, characterized in that: It also includes cerium chloride accounting for 10-15% of the mass of the aluminum fluoride and strontium chloride accounting for 3-3.2% of the mass of the aluminum fluoride.
5. A method for preparing the nickel removal agent for aluminum liquid according to any one of claims 1 to 4, characterized in that: The specific preparation steps include: Carbon coating of spherical nano-alumina: The spherical nano-alumina is subjected to chemical vapor deposition to coat the surface of the spherical nano-alumina with an organic precursor, and then naturally cooled to room temperature in an inert gas atmosphere to obtain carbon-coated spherical nano-alumina; Preparation of the product: Weigh each component according to the raw material composition, first mix aluminum fluoride, magnesium chloride, zinc chloride and sodium chloride by ball milling, and then stir and mix them with carbon-coated spherical nano-alumina to obtain the product.
6. The method for preparing a nickel remover for aluminum liquid according to claim 5, characterized in that: The chemical vapor deposition comprises: using acetylene gas as a carbon source, performing chemical vapor deposition at a temperature of 1000-1100° C. and a gas flow rate of 380-400 L / min, and adjusting the specific chemical vapor deposition time to adjust the coating amount of amorphous carbon on the surface of the spherical nano-alumina to 4.2-4.8% of the mass of the spherical nano-alumina.
Citation Information
Patent Citations
Molten aluminum denickel agent
CN103184350A